Problems of Learning Shorof in Mashdar Ghairu Mim of Students at Ar-Roudhoh Tahfidz Masaran Sragen Islamic Boarding School for the 2025/2026 Academic Year - Dawud, Abii (Maharaat: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to describe the process and method of learning shorof, identify the problems faced by students, and analyze solutions to overcome these problems in class III of KMI Ar-Roudhoh Tahfidz Preneur Masaran Sragen Islamic Boarding School. This study uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis uses Miles and Huberman's interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that: 1) Shorof science learning uses four main methods, namely lecture methods, memorization, question and answer, and imla'. 2) Learning problems are divided into two, namely linguistic problems (phonology/sounding, morphology/word change, and mufrodat) and non-linguistic problems (time limitations, heterogeneity of students' abilities, and low motivation to memorize tashrif). 3) Solutions to overcome these problems include collaboration with tahsin/tajweed and nahwu teachers, habituation of istima' (listening), grouping students based on ability, addition of lesson hours or enrichment programs, and the use of varied learning methods such as tashrif pronunciation using tone.